2023
DOI: 10.1590/1806-9061-2022-1682
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Efficacy Assessment of Ethanolic and Aqueous Extracts of Cinnamon (Cinnamomum Verum) Bark against Selected Microbes

Abstract: To combat pathogens and reduce the major public health problem of antibiotic residues in animal products, scientists are looking for natural antibiotic substitutes that are effective against drug-resistant pathogenic microbes and spoilage fungi. The antimicrobial activity of three Cinnamomum verum extracts prepared with three different solvents (absolute ethanol, 50% ethanol, and aqueous extracts) was determined against two Gram-positive bacteria (Staphylococcus aureus and Listeria monocytogenes) and two Gram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…This study showed that this EO and its main component, cinnamaldehyde, exhibited strong antifungal activity at 50-100 ppm [27]. Our results and those of published works [28][29][30][31] agree that EOs from cinnamon bark or from clove bud possess a broad-spectrum antifungal activity.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that this EO and its main component, cinnamaldehyde, exhibited strong antifungal activity at 50-100 ppm [27]. Our results and those of published works [28][29][30][31] agree that EOs from cinnamon bark or from clove bud possess a broad-spectrum antifungal activity.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, the world has been striving to use antibiotic alternatives, including essential oils ( EOs ) and their nano-emulsions ( Sharma et al, 2023 ), probiotics ( Abd El‐Hack et al, 2020 ), amino acids ( Gelinski et al, 2023 ), herbal extracts ( Al-Garadi et al, 2022 ; Al-Garadi et al, 2023a ), and green nanoparticles ( Abd El-Ghany et al, 2021 ) to improve birds’ performance, control pathogens and avoid antibiotics resistance and misuse risks.…”
Section: Introductionmentioning
confidence: 99%